Cross-linked polymersomes as nanoreactors for controlled and stabilized single and cascade enzymatic reactions - Graefe, David; Gaitzsch, Jens; Appelhans, Dietmar; Voit, Brigitte (Nanoscale, 2014)
Polymeric vesicles or polymersomes are one of the supramolecular entities at the leading edge of synthetic biology. These small compartments have shown to be feasible candidates as nanoreactors, especially for enzymatic reactions. Once cross-linked and equipped with a pH sensitive material, the reaction can be switched off (pH 8) and on (pH 6) in accordance with the increased permeability of the polymersome membranes under acidic conditions. Thus cross-linked and pH sensitive polymersomes provide a basis for pH controlled enzymatic reactions where no integrated transmembrane protein is needed for regulating the uptake and release of educts and products in the polymersome lumen. This pH-tunable working tool was further used to investigate their use in sequential enzymatic reactions (glucose oxidase and myoglobin) where enzymes are loaded in one common polymersome or in two different polymersomes. Crossing membranes and overcoming the space distance between polymersomes were shown successfully, meaning that educts and products can be exchanged between enzyme compartments for successful enzymatic cascade reactions. Moreover the stabilizing effect of polymersomes is also observable by single enzymatic reactions as well as a sequence. This study is directed to establish robust and controllable polymersome nanoreactors for enzymatic reactions, describing a switch between an off (pH 8) and on (pH 6) state of polymersome membrane permeability with no transmembrane protein needed for transmembrane exchange. © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-20